HGG-35. IDENTIFICATION OF G PROTEIN-COUPLED RECEPTOR 17 (GPR17) UP-REGULATION IN PAEDIATRIC H3 K27M-MUTANT DIFFUSE MIDLINE GLIOMA AND EXAMINATION OF ITS ROLE IN DIFFUSE MIDLINE GLIOMA CELL LINES. (1st June 2021) - Loveson, Katie; Fillmore, Helen
Abstract: Paediatric H3 K27M-mutant diffuse midline glioma (pDMG) is an incurable, aggressive childhood brain malignancy, that arises in a region- and age-specific nature. The underlying pathophysiology suggests dysregulation of postnatal neurodevelopmental processes causing aborted cell differentiation. The cell of origin is unclear, but data suggests an oligodendrocytic lineage (OPC), supported by the over-expression of transcription factors such as Olig1 and Olig2 in 80% of DIPG cases. In-depth bioinformatics and principal component analyses (PCA) of genes involved in brain development and pDMG support reports of OPC gene dysregulation and led to the identification of the G-protein coupled receptor 17 (GPR17) and its association with pDMG. GPR17, a rhodopsin-like orphan GPCR (unknown ligand), has the typical features of the GPCR superfamily, seven transmembrane domains (TM1-TM7), eight amphipathic helices, an extracellular N-terminal domain, and an intracellular C-terminus. GPR17 has been implicated in several normal physiological and pathological processes, such as oligodendrocyte differentiation, spinal cord injury and brain injury. GPR17 mRNA and protein expression was confirmed in all pDMG cell lines tested. Using a well-characterised agonist (MDL 299, 51) and antagonist (HAMI3379) to modulate GPR17 function in pDMG cell lines resulted in phenotypic and genomic changes as well as in cell growth and migration. HAMI3379, a GPR17 specific antagonist resulted in a significant reduction in GPR17 mRNA and protein expression (p<0.006) and a significant reduction in migration (p<0.0025). When pDMG cells were pretreated with HAMI3379 in combination with known cytotoxic agents (Bleomycin, a radiation mimic, Panobinostat or Vincristine), there was a decrease in cell viability compare to cytotoxic agent alone. There are no current effective therapies for pDMG patients and the ability of blocking GPR17 function to enhance sensitivity to standard therapies is appealing and warrants further investigation.